Characteristics and evolution of brown carbon in western United States wildfires - L. Zeng; J. Dibb; E. Scheuer; J. M. Katich; J. M. Katich; J. P. Schwarz; I. Bourgeois; I. Bourgeois; J. Peischl; J. Peischl; T. Ryerson; T. Ryerson; et al. (Atmospheric Chemistry and Physics, 2022)
Brown carbon (BrC) associated with aerosol particles in western United States wildfires was measured between July and August 2019 aboard the NASA DC-8 research aircraft during the Fire Influence on Regional to Global Environments and Air Quality (FIREX-AQ) study. Two BrC measurement methods are investigated, highly spectrally resolved light absorption in solvent (water and methanol) extracts of particles collected on filters and in situ bulk aerosol particle light absorption measured at three wavelengths (405, 532 and 664 nm) with a photoacoustic spectrometer (PAS). A light-absorption closure analysis for wavelengths between 300 and 700 nm was performed. The combined light absorption of particle pure black carbon material, including enhancements due to internally mixed materials, plus soluble BrC and a Mie-predicted factor for conversion of soluble BrC to aerosol particle BrC, was compared to absorption spectra from a power law fit to the three PAS wavelengths. For the various parameters used, at a wavelength of roughly 400 nm they agreed, at lower wavelengths the individual component-predicted particle light absorption significantly exceeded the PAS and at higher wavelengths the PAS absorption was consistently higher but more variable. Limitations with extrapolation of PAS data to wavelengths below 405 nm and missing BrC species of low solubility that more strongly absorb at higher wavelengths may account for the differences. Based on measurements closest to fires, the emission ratio of PAS-measured BrC at 405 nm relative to carbon monoxide (CO) was on average 0.13 Mm−1 ppbv−1; emission ratios for soluble BrC are also provided. As the smoke moved away from the burning regions, the evolution over time of BrC was observed to be highly complex; BrC enhancement, depletion or constant levels with age were all observed in the first 8 h after emission in different plumes. Within 8 h following emissions, 4-nitrocatechol, a well-characterized BrC chromophore commonly found in smoke particles, was largely depleted relative to the bulk BrC. In a descending plume where temperature increased by 15 K, 4-nitrocatechol dropped, possibly due to temperature-driven evaporation, but bulk BrC remained largely unchanged. Evidence was found for reactions with ozone, or related species, as a pathway for secondary formation of BrC under both low and high oxides of nitrogen (NOx) conditions, while BrC was also observed to be bleached in regions of higher ozone and low NOx, consistent with complex behaviors of BrC observed in laboratory studies. Although the evolution of smoke in the first hours following emission is highly variable, a limited number of measurements of more aged smoke (15 to 30 h) indicate a net loss of BrC. It is yet to be determined how the near-field BrC evolution in smoke affects the characteristics of smoke over longer timescales and spatial scales, where its environmental impacts are likely to be greater.